Researches on the I Ching - Researches on the I. Ching / by Iulian K. Shchutskii ; translated by William L. MacDonald and Tsuyoshi Hasegawa with Hellmut Wilhelm ; with an introduction by Gerald W. Swanson (Princeton legacy library., 2017)
A noted Russian sinologue, Iulian Shchutskii tried to find out how the I China was put together and what the terms meant when they were written. Accordingly, he goes back to the original text, studies the structure of its language, and examines its concepts in terms of its own images and ideas rather than through the preconceived constructs with which most Western scholars approach the book. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.